Mutant Enpp1(asj) mice as a model for generalized arterial calcification of infancy - Li, Qiaoli (The Company of Biologists Limited, 2013)
Generalized arterial calcification of infancy (GACI), an autosomal recessive disorder, is characterized by early mineralization of blood vessels, often diagnosed by prenatal ultrasound and usually resulting in demise during the first year of life. It is caused in most cases by mutations in the ENPP1 gene, encoding an enzyme that hydrolyzes ATP to AMP and inorganic pyrophosphate, the latter being a powerful anti-mineralization factor. Recently, a novel mouse phenotype was recognized as a result of ENU mutagenesis – those mice developed stiffening of the joints, hence the mutant mouse was named ‘ages with stiffened joints’ (asj). These mice harbor a missense mutation, p.V246D, in the Enpp1 gene. Here we demonstrate that the mutant ENPP1 protein is largely absent in the liver of asj mice, and the lack of enzymatic activity results in reduced inorganic pyrophosphate (PP(i)) levels in the plasma, accompanied by extensive mineralization of a number of tissues, including arterial blood vessels. The progress of mineralization is highly dependent on the mineral composition of the diet, with significant shortening of the lifespan on a diet enriched in phosphorus and low in magnesium. These results suggest that the asj mouse can serve as an animal model for GACI.